PETROGRAFI KARAKTERISTIK BATUPASIR FORMASI GAMPING WUNGKAL IMPLIKASI UNTUK PROVENAN, DIAGENESIS, DAN PROSES PENGENDAPAN, FORMASI GAMPING WUNGKAL, KECAMATAN BAYAT, KABUPATEN KLATEN, PROVINSI JAWA TENGAH - Pangestu, Aaf Aji; Wiloso, Danis Agoes (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2019)
Gamping Wungkal Formation, middle Eocene to Upper Eocene, which consists of sandstones, sandy marl, claystone and limestone which are the problems of provenance rock, diagenesis and its deposition process. Retrieval of stratigraphic data to determine the deposition process which is divided into several facies and determine its depositional environment, petrographic observations to determine the type of rock, provenance, tectonic settings. Interpretation of tectonic settings of sandstones Gamping Wungkal Formations on QFL diagram plots include recycled orogens, foreland uplift sub-zones while the plot in the QmFLt diagram of the provenance rock is the same as the QFL diagram, which is recycled orogen, sub-zone foreland uplift, rock model from recycled orogen foreland uplift sub-zone. The sandstone diagenesis of the Gamping Wungkal Formation in the study area is included in the mesodiagenesis stage where the compaction or burial process still dominates, the depositional environment in the study area is an area formed in the transitional environment or intertidal flat (Middle tidal flat) and subtidal (Lower tidal flat).